Reviews of environmental contamination and toxicology. volume 211 - Whitacre, David M. (Reviews of environmental contamination and toxicology, continuation of residue reviews, 2011)
CONTENTS Foreword Preface The Water Quality of Izmir Bay: A Case Study by Filiz Kucuksezgin Teratogenicity and Embryotoxicity in Aquatic Organisms after Pesticide Exposure and the Role of Oxidative Stress by Veronika Pa?ková, Klára Hilscherová and Lud?k Bláha Mixtures of Environmental Pollutants: Effects on MIcroorganisms and their Activities in Soils by B. Ramakrishnan, M. Megharaj, K. Venkateswarlu, N. Sethunathan and R. Naidu Fluoride in the Environment and its Metabolism in Humans by Sunil Kumar Jha, Vinay Kumar Mishra, Dinesh Kumar Sharma and Thukkaram Damodaran Index.